国际管制药物供应情况： 确保医疗和科研所用药物的充分供应 - United Nations Office on Drugs; Crime (United Nations, 2016)
This supplement to the INCB’s Annual Report 2015 analyses global access to narcotic drugs and psychotropic substances. The report provides an introduction to the drug control conventions, human rights, action taken by the Board, and the report’s methodology. It focuses on narcotic drugs, examining supply and demand of opiate raw materials and opioids, availability of opioid analgesics, and impediments to their access for medical and scientific purposes, while analysing the situation of psychotropic substances, considering their use as analgesics, anti-epileptics, anxiolytics, sedative-hypnotics and stimulants. It also covers the topic of availability of internationally controlled drugs for the treatment of opioid dependence, and looks into simplified provision in emergency situations.